2022-RA-1259-ESGO Brachytherapy and surgery versus surgery alone for IB2 (FIGO 2018) cervical cancers: A FRANCOGYN study. (20th October 2022) - Aissaoui, Othman; Phalipou, Jérôme; Cordoba, Abel; Azais, Henri; Ouldamer, Lobna; Bolze, Pierre Adrien; Ballester, Marcos; Huchon, Cyrille; Mimoun, Camille; Akladios, Cherif; Lecointre, Lise; Raimond, Emilie; et al.
Abstract : Introduction/Background: Evaluation of the management by first brachytherapy followed by enlarged hysterectomy (Wertheim type) compared to enlarged surgery alone (Wertheim type) for the treatment of IB2 cervical cancer. Methodology: Data from women with histologically proven FIGO stage IB2 cervical cancer treated between April 1996 and December 2016 were retrospectively abstracted from twelve French institutions with prospectively maintained databases. Results: Of the 211 patients with FIGO stage IB2 cervical cancer without lymph node involvement included, 136 had surgical treatment only and 75 had pelvic lymph node staging and brachytherapy followed by surgery. The surgery-only group had significantly more adjuvant treatment (29 vs. 3; p = 0.0002). A complete response was identified in 61 patients (81%) in the brachytherapy group. Postoperative complications were comparable (63, 2% vs. 72%, p=0, 19) and consisted mainly of urinary (36 vs. 27) and digestive (31 vs 22) complications and lymphoceles (4 vs. 1). Brachytherapy had no benefit in terms of progression-free survival (p=0.14) or overall survival (p=0.59). However, for tumors in between 20 and 30 mm, preoperative brachytherapy improved recurrence-free survival (p = 0.0095) but not overall survival (p = 0.41). This difference was not observed for larger tumors in terms of either recurrence-free survival (p = 0.55) or overall survival (p = 0.95). Conclusion: Our study found that preoperative brachytherapy had no benefit for stage IB2 cervical cancers in terms of recurrence-free survival or overall survival. For tumor sizes between 2 and 3 cm, brachytherapy improves progression-free survival mainly by reducing pelvic recurrences without improving overall survival.